If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-12=15=
We move all terms to the left:
-3x-12-(15)=0
We add all the numbers together, and all the variables
-3x-27=0
We move all terms containing x to the left, all other terms to the right
-3x=27
x=27/-3
x=-9
| –14g−17=–18g+16+19 | | 13=11-4x= | | -14+16d=17d | | m/2=17 | | -10+2z=10-8z | | 7=w+2.5. | | -6(2x-9)+6x=-7 | | (-20-10y)+y=-2 | | -10+2z=10−8z | | 4(2h+3)=2(5h-2)+6;h | | –10+2z=10−8z | | 5(x-2)=4(2x+5);x | | 5(x−2)=4(2x+5);x | | 7y+5=3y+17;y | | 7+5(x-2)=5-9(x-5) | | 6-3a=21= | | x+2x=1-16;x |